2009
DOI: 10.1002/ccd.22236
|View full text |Cite
|
Sign up to set email alerts
|

Transradial simultaneous kissing stenting (SKS) with SheathLess access

Abstract: Transradial coronary intervention is usually performed via a 5 or 6 Fr sheath due to the small calibre of radial arteries. Simultaneous kissing stenting (SKS) technique requires a guiding catheter 7 Fr or larger and is therefore difficult to perform via transradial approach. Conversion to femoral approach or additional arterial access is usually required to achieve this goal. To overcome this limitation, a hydrophilic 7.5 Fr SheathLess guiding catheter can be exploited. This catheter possesses approximately th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…proximal protection, thrombectomy devices, and simultaneous kissing stenting 7)8). In our study, we successfully performed three complex procedures including two in which the kissing balloon technique was used and one in which the modified T-stenting technique was used.…”
Section: Discussionmentioning
confidence: 95%
“…proximal protection, thrombectomy devices, and simultaneous kissing stenting 7)8). In our study, we successfully performed three complex procedures including two in which the kissing balloon technique was used and one in which the modified T-stenting technique was used.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, recent studies have shown that the sheathless catheter can be successfully used in complex procedures requiring the use of at least 6‐F and even 7‐F GC .…”
Section: Discussionmentioning
confidence: 99%
“…Sheathless guiding catheter systems consisting in a hydrophilic catheter with a central dilator that does not require an introducer sheath during transradial PCI offer a larger lumen than a conventional guiding catheter inserted through a sheath introducer of similar outer diameter. These systems have been shown effective for treatment of complex coronary lesions, including bifurcations, and may represent another alternative to 5 French guiding catheters in patients with a small radial artery . Such an opportunity needs to be gauged against higher costs and potential stability and safety issues related to the hydrophilic coating and increased stiffness compared to conventional guiding catheters …”
Section: Discussionmentioning
confidence: 99%